2018
DOI: 10.7251/jepm181002001a
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented maize - a potential source of β-carotene and α-tocopherol

Abstract: Among cereals, maize has the highest content of bioavailable micronutrients in grain, particularly β-carotene and α-tocopherol, which makes this crop the most appropriate for biofortification. Great genetic variability is a valuable source of micronutrients, and genotypes with enhanced grain content could be used for improvement of commercial hybrids or synthetic populations creation. Three populations with dark orange, dark red and red grain, five elite lines, and their crosses were evaluated for β-carotene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Besides increase of single nutrient content, simultaneous breeding for multinutritional traits have numerous beneficial effects. In the study Andelković et al (174) micronutrient content in three colored grain populations, five inbred lines and their crosses were evaluated. Population with dark orange grain had high content of both, β-carotene (26.9 µg/g d.m.)…”
Section: Breeding Programsmentioning
confidence: 99%
“…Besides increase of single nutrient content, simultaneous breeding for multinutritional traits have numerous beneficial effects. In the study Andelković et al (174) micronutrient content in three colored grain populations, five inbred lines and their crosses were evaluated. Population with dark orange grain had high content of both, β-carotene (26.9 µg/g d.m.)…”
Section: Breeding Programsmentioning
confidence: 99%
“…Across the globe, there are different varieties of corn, which is rich in fiber, vitamins, minerals, phenolic acids, flavonoids, sterols, and a great variety of phytochemicals [ 115 ]. There are reports that indicate that corn is one of the cereals with the highest availability of nutrients, mainly β-carotene and α-tocopherol, which suggests that it may be the most suitable for biofortification [ 116 ]. However, this may depend on the pigments in the grain.…”
Section: Cereals As a Source Of Compounds With Anti-hypertensive Acti...mentioning
confidence: 99%
“…Yellow corn is rich in carotenoids with a concentration of 0.823 mg/100 g per dry weight of corn [ 119 ]. Violeta et al [ 116 ] have reported concentrations of 26.9 μg/g of β-carotene and 27.2 μg/g of α-tocopherol in dark orange corn grains, while in dark red corn, they were 2.51 and 4.95 μg/g, respectively, and in red corn, they only reported a concentration of α-tocopherol of 4.87 μg/g. Pigmented genotypes have shown a strong antioxidant capacity using DPPH and TEAC techniques [ 120 ].…”
Section: Cereals As a Source Of Compounds With Anti-hypertensive Acti...mentioning
confidence: 99%